Interpretation of micromorphological features of soils and regoliths - Stoops, Georges; Marcelino, Vera; Mees, F. (Florias) (Elsevier, 2018)
Interpretation of Micromorphological Features of Soils and Regoliths, Second Edition, provides researchers and students with a tool for interpreting features observed in soil thin sections and through submicroscopic studies. After an introduction and general overview, micromorphological aspects of regoliths (e.g., saprolites, transported materials) are highlighted, followed by a systematic and coherent discussion of the micromorphological expression of various pedogenic processes. The book is written by an international team of experts in the field, using a uniform set of concepts and terminology, making it a valuable interdisciplinary reference work. The following topics are treated: freeze-thaw features, redoximorphic features, calcareous and gypsiferous formations, textural features, spodic and oxic horizons, volcanic materials, organic matter, surface horizons, laterites, surface crusts, salt minerals, biogenic and pedogenic siliceous materials, other authigenic silicates, phosphates, sulphidic and sulphuric materials, and features related to faunal activity. The last chapters address anthropogenic features, archaeological materials and palaeosoils.